G408(P) The production of a diabetes information film, by young people who have diabetes, as a means of educating others. (12th March 2018) - Dublon, VE; Green, S; Benitez-Castillo, M; Edwards, T; Leiva, A
Abstract : Method: After establishing a group of regular attendees to our Diabetes Education Days we wanted to make these more patient centred. We obtained a grant from the Diabetes Research and Wellness Foundation. Through the medium of puppet making and learning film skills the young people felt empowered producing their own educational film. Throughout the process, of four sessions spread over four weeks, the young people were supported by a multidisciplinary team consisting of consultant paediatrician, a specialist diabetes nurse, the deputy head of the Hospital school, a dietician, a team of professional puppet makers, and a film making expert. In addition to filming the actual process, the participants wrote and filmed their individual screenplays. There was opportunity to explore individual experiences and knowledge of diabetes in a fun, non-judgemental setting. Full consent was given by all attendees regarding the final distribution and use of the film. Results: The first of four sessions was a resounding success. Young people were desperate to attend the following sessions, altering schedules to ensure they could make them. During the process it became very clear they would like the film to be used as an educational tool. The response to the first viewing has given great verbal feedback and we are now in the process of collating formal qualitative data from the following groups: Children at the Royal Free Hospital School without diabetes, those with a new diagnosis and those who already have diabetes, which will be ready to be shared at the conference. Conclusion: Young people with diabetes embraced these sessions with huge enthusiasm. Having previously not known each other they quickly formed friendships and all actively took part, encouraging each other. They expressed and explored their knowledge in a relaxed environment, very different from clinic; given a rare and valuable opportunity to fully voice their opinions. At the same time, they loved the idea that the film productions they contributed to may go on to help other people. For the professionals it was an incredibly inspiring experience and the film really does show diabetes through the eyes of the young people themselves.